Heterocyclic Schiff base transition metal complexes in antimicrobial and anticancer chemotherapy. Issue 3 (5th January 2018) - Malik, Manzoor Ahmad; Dar, Ovas Ahmad; Gull, Parveez; Wani, Mohmmad Younus; Hashmi, Athar Adil
Abstract : Schiff-base transition metal complexes display amazing antimicrobial and anticancer activities. Abstract : In recent years, the number of people suffering from cancer and multidrug-resistant infections has sharply increased, leaving humanity without any choice but to search for new treatment options and strategies. Although cancer is considered the leading cause of death worldwide, it also paves the way many microbial infections and thus increases this burden manifold. Development of small molecules as anticancer and anti-microbial agents has great potential and a plethora of drugs are already available to combat these diseases. However, the wide occurrence of multidrug resistance in both cancer and microbial infections necessitates the development of new and potential molecules with desired properties that could circumvent the multidrug resistance problem. A successful strategy in anticancer chemotherapy has been the use of metallo-drugs and this strategy has the potential to be used for treating multidrug-resistant infections more efficiently. As a class of molecules, Schiff bases have been the topic of considerable interest, owing to their versatile metal chelating properties, inherent biological activities and flexibility to modify the structure to fine-tune it for a particular biological application. Schiff base-based metallo-drugs are being researched to develop new anticancer and anti-microbial chemotherapies and because both anticancer and anti-microbial targets are different, heterocyclic Schiff bases can be structurally modified to achieve the desired molecule, targeting a particular disease. In this review, we collect the most recent and relevant literature concerning the synthesis of heterocyclic Schiff base metal complexes as anticancer and anti-microbial agents and discuss the potential and future of this class of metallo-drugs as either anticancer or anti-microbial agents.